Comparative experimental optical studies on 7.O5O.7 dimeric liquid crystal compound using theoretical models. Issue 4 (16th March 2018) - Bhattacharjee, Debanjan; Alapati, Parameswara Rao; Bhattacharjee, Ayon
ABSTRACT: In the present study, the optical properties of the 7.O5O.7 dimeric compound are reported. This dimeric compound exhibits typical smectic A to smectic F phase transition, and the main focus of our study is to observe the optical behaviour in SmA phase. In the dimeric compound, the two mesogens are connected by a linkage group or spacer. The presence of the linkage group and the terminal alkyl chains plays a vital role to change the behaviour of this compound as compared to the traditional monomeric compounds. Study of birefringence, refractive indices and normalised polarisation are essential to investigate the optical nature in liquid crystalline compounds. The optical study in our compound is carried out by using the thin prism experimental method with the help of He-Ne laser of wavelength 633 nm. Four-parameter model was used to obtained theoretically measured refractive indices and birefringence data. The theoretical results are then compared with the experimental results. Both the experimentally and theoretically calculated results are properly fitted in our dimeric compound. Graphical Abstract: